2015
DOI: 10.4236/aim.2015.54021
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serotypes, Susceptibility to Macrolide and Virulence and Resistance Molecular Profiles in Invasive Strains of <i>Streptococcus agalactiae</i> in Two Argentine Provinces

Abstract: How to cite this paper: Laczeski, M., et al. (2015)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In a study carried out with strains that cause invasive diseases in the province of Misiones, all genes were detected in 72.73% of the isolates and it is observed that the strains recovered from neonates present all the virulence factors in percentages greater than 81.80%. However, the number of isolates analyzed was lower (n = 11) despite belonging to all invasive isolates recovered simultaneously during the years in which the present study was conducted [62].…”
Section: Molecular Detection Of Virulence-associated Genesmentioning
confidence: 77%
“…In a study carried out with strains that cause invasive diseases in the province of Misiones, all genes were detected in 72.73% of the isolates and it is observed that the strains recovered from neonates present all the virulence factors in percentages greater than 81.80%. However, the number of isolates analyzed was lower (n = 11) despite belonging to all invasive isolates recovered simultaneously during the years in which the present study was conducted [62].…”
Section: Molecular Detection Of Virulence-associated Genesmentioning
confidence: 77%